Context-Aware Ubiquitous Learning Based on Case Methods and Team-Based Projects: Design and Validation - I Kadek Suartama; Eges Triwahyuni; Kadek Suranata (MDPI AG, 2022)
Since the development of information and communication technology 'learning media' have been recognized as increasingly important courses by educators to assist students training to be professional teachers to understand the process of designing, developing, utilizing, managing, and evaluating learning resources. The context-aware ubiquitous learning approach design based on case methods and team-based projects has been proposed to guide activities in the student learning process. Therefore, this research aims to describe the design and determine the feasibility or validity of context-aware ubiquitous learning based on case methods and a team-based project model using the research and development (R&D) approach. The procedure consists of (1) model development and (2) product validation. It is important to note that the validation aspect involved five learning material/design experts, five 'learning media' experts, and 162 students from state and private universities in Indonesia after which the data obtained from experts and students were analyzed using the descriptive statistics. The results showed that the learning model designed is suitable for use in the student learning process.